Dental anatomy of the apex predator Sinraptor Dongi (Theropoda: Allosauroidea) from the late Jurassic of China - Hendrickx, Christophe Marie Fabian (2020)
The dental morphology of the holotype of the theropod Sinraptor dongi from the Jurassic Shishugou Formation of China is comprehensively described. We highlight a combination of dental features that appear to be restricted to Sinraptor: (i) crowns with denticulated mesial and distal carinae extending from the root and an irregular surface texture on the enamel; (ii) a D- to salinon-shaped cross-sectional outline at the crown base in mesialmost teeth; (iii) mesial crowns with mesial carinae spiraling mesiolingually and lingually positioned longitudinal groove adjacent to the mesial carina; and (iv) particularly labiolingually compressed lateral teeth with weakly labially deflected distal carinae, flat to concave basocentral surfaces of the labial margins of the crowns, and horizontally elongated distal denticles showing short to well-developed interdenticular sulci. Using cladistic, multivariate, discriminant, and cluster analyses, we demonstrate that the dentition of Sinraptor is relatively similar to that of ceratosaurids, megalosauroids, and other allosauroids and is particularly close to that of Allosaurus. The dental anatomy of Sinraptor and Allosaurus, which differs mainly in the labiolingual compression of the lateral crowns and in the number of premaxillary teeth, shows adaptations towards a predatory lifestyle, including premaxillary teeth capable of enduring tooth-tobone contact and crowns with widely separated mesial and distal carinae capable of inflicting widely open wounds.